ANALYSIS OF THE ROLE OF FAMILY DA'WAH IN BUILDING CHILDREN'S RESILIENCE TO THE INFLUENCE OF ONLINE GAMBLING - Putri, Delfiya Duwita; Sunata, Ivan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
The rise of online gambling has become a serious issue in Indonesia, particularly concerning its impact on children. This phenomenon raises deep concerns about the negative effects it may have on their development and well-being. In this context, the role of family preaching (dakwah) is crucial in strengthening children's resilience against the negative influences of online gambling. This research aims to analyze how family preaching can contribute to building resilience in children against the risks of online gambling. To achieve this objective, the study adopts a descriptive qualitative approach and utilizes a library research method, hoping to provide an in-depth understanding of the role of family preaching in protecting children from the negative impacts of online gambling, as well as to identify effective preaching strategies. This involves gathering relevant information or scholarly works such as books, journal articles, internet articles, websites, and YouTube videos. The results indicate that there are several roles of family preaching in shaping children's resilience against online gambling: First, parents act as pioneers by teaching religious values; Second, as protectors from dangers such as online gambling; Third, as advisors by respecting children's viewpoints; Fourth, as role models in responsibility and morality; Fifth, by implementing clear rules; and Sixth, through balanced supervision to monitor children's behavior. Parents must also balance freedom and support to foster children's development.